PEMANFAATAN CLOUD COMPUTING UNTUK KOLABORASI RISET DAN PENGEMBANGAN SOLUSI PENDIDIKAN DI INSTITUT MAHARDIKA CIREBON - Ramadhan, Syaiful; Sutriyono, Ade; Rosmawan, Hendri (Awatara Publisher, 2026)
The shift towards digital transformation in higher education demands effective collaborative tools for research and learning. This study aims to analyze the utilization of cloud computing for research collaboration and the development of educational solutions among lecturers and students at Institut Mahardika, Cirebon. This research uses a quantitative descriptive method with a survey approach, involving 85 respondents. Data were collected through questionnaires and analyzed using descriptive statistics. The results show that the adoption of cloud computing significantly increases research productivity and cross-disciplinary collaboration efficiency. The data indicates an 82% increase in the speed of data sharing and co-authoring processes. Furthermore, cloud platforms enable the rapid development of educational solutions, such as centralized e-learning repositories. In conclusion, cloud computing is not just a storage medium but a vital catalyst for academic innovation. This study confirms that proper integration of cloud infrastructure, supported by adequate digital literacy, can solve spatial and temporal barriers in academic environments